Efectos de la aplicación de la abonadura orgánica en tres mezclas forrajeras en terrenos con pendientes mayores al30%, en el cantón Tulcán, provincia del Carchi - Cerón Benavides, Oscar Daniel (2013)
This research was conducted in the field Myrtle, located in Barrio San José of the parish Pioter, Canton Tulcan Carchi. The area is characterized by cold weather, with an average temperature of 16 ° C, varying from a minimum of 4 ° C to a maximum of 28 ° C in summer t imes. They are deep soils with sandy texture, located at 2900 m asl The main objective was to determine the effects of application of organic Fertilisation and adaptability of three forage mixtures on land with slopes greater than 30%. The specific objectives were to identify the forage mixture greater adaptability and performance, evaluate the application of organic matter on the adaptability of three forage mixtures on land with slopes greater than 30%, and economically analyze treatments to determine crop profitability.